2004
DOI: 10.1021/jf035381p
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Composition of Melanoidins from Glucose and Maltose

Abstract: The composition of melanoidins formed in the reactions of either glucose or maltose with glycine (70 degrees C, pH 5.5, [glucose] = [maltose] = [glycine] = 0.25 M) (MW > 3500) was investigated by microanalysis and the use of (14)C-labeled sugars and amino acid. The most reliable parameter obtained from microanalysis data is the C/N value, as it was calculated with no model assumption. The C/N value (7.6 +/- 0.2 for glucose and 10.5 +/- 0.2 for maltose) does not change with molecular weight (MW > 3500) as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…As reported in the literature ( , ), products originating from the released monosaccharide are also found in the Maillard reaction of the parent disaccharide. In the kinetic model presented here, we believe that the glycosidic bond of maltose can be broken and that glucose is released by a mechanism where the 4-substituted intermediate I1 is converted to I3, which in the specific case of maltose is 3,4-dideoxyhexosulos-3-ene DDH, by analogy to the loss of a water molecule as 3-DH is converted to DDH in the glucose−glycine reaction.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…As reported in the literature ( , ), products originating from the released monosaccharide are also found in the Maillard reaction of the parent disaccharide. In the kinetic model presented here, we believe that the glycosidic bond of maltose can be broken and that glucose is released by a mechanism where the 4-substituted intermediate I1 is converted to I3, which in the specific case of maltose is 3,4-dideoxyhexosulos-3-ene DDH, by analogy to the loss of a water molecule as 3-DH is converted to DDH in the glucose−glycine reaction.…”
Section: Resultssupporting
confidence: 72%
“…The kinetic model proposed here for the maltose-glycine reaction is based on the best available understanding of the key steps in the browning of maltose as illustrated in Figure 1, whereby we consider two distinct routes by which maltose can form melanonidins with glycine as already reported (13) in an investigation into the composition of melanoidins from glucose and maltose. First, the maltose residue can remain intact to be incorporated whole as the melanoidins increase in size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors report that in a model system the C/N ratio in melanoidins is high in the initial reaction period and decreases as the reaction time increases (10). The C/N ratio also decreases at lower temperatures or pH values (11). Cammerer et al (12) found that maltose forms melanoidins with a lower nitrogen content than do other disaccharides such as lactose and sucrose.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoidins generated in the reactions of glucose and maltose with glycine (MW >12500 and 3500) was studied by microanalysis. Finally, the relationship between the molecular weight of the Melanoidins and the elemental composition of amino acids and sugars was discussed [21]. Cämmerer et al [22] used molecular weights of 12000-14000 Da cellulose dialysis membranes to analyze the MRPs before and after the dialysis, respectively.…”
Section: E Pretreatment For Phmrps Analysismentioning
confidence: 99%